Evaluasi Kepemimpinan Presiden Joko Widodo Menjelang Akhir Masa Jabatan - Iwan Sumiarsa; Hidayat Hidayat; Siti Nur Azijah; Yusup Supendi; Muhammad Husein Maruapey; Agus Suarman Sudarsa (Ministrate: Jurnal Birokrasi dan Pemerintahan Daerah, 2023)
In 2024 Joko Widodo will end his tenure as President with a series of polemics at the end of his tenure. He was considered not neutral in the presidential election contest because he openly stated that he would not be neutral for the sake of the nation and state. His statement immediately received responses from various groups because he considered that what Jokowi was doing was a step to secure various projects that are still experiencing problems, such as the National Capital project which is still hampered by development investment and the Jakarta-Bandung Fast Railroad project which is experiencing swelling. cost. President Jokowi's policies must certainly receive an evaluation so that in the future what has not been done by Jokowi can be followed up by the next President, especially employment and poverty problems which until now have not been optimally resolved. This research was conducted to assess President Jokowi's performance by analyzing various sources so that it can be found what Jokowi has achieved and what he has not done. Using a descriptive methodology, the author will describe the results of the author's analysis and observations from various sources of electronic media and journals that discuss President Jokowi's performance, for further comments